EFFECT OF DIGITAL DETOXIFICATION ON PSYCHOLOGICAL WELL-BEING: A NEWER HEALTH AND WELLNESS TREND IN THE CURRENT ERA (Contemporary Journal of Social Science Review, 2025)
With increasing reliance on digital devices, concerns about their impact on mental health have grown, particularly among young adults. The growing concern over the negative impact of excessive digital media use has led to the emergence of digital detox interventions, which aim to mitigate these risks by encouraging individuals to disconnect from their digital devices for specific periods. This study aims to investigate the impact of a digital detox as intervention on psychological well-being among young adults. Sample of 40 students were targeted for their high digital device usage. Digital Detox Practices Questionnaire (Anandpara et al., 2024) and Psychological Wellbeing Scale (Ryff, 1989) were used as research instruments to measure study variables. Data were analyzed using Paired Samples t-Test on SPSS.  Participants’ psychological well-being was assessed before and after a two-week-long digital detox intervention, which encouraged reduced digital device usage. Findings indicated statistically significant improvements in psychological well-being scores post-intervention, with p-values < .0001 for all comparisons. Students’ mean score of autonomy, environmental mastery, personal growth, positive relations, purpose in life and self-acceptance was enhanced by digital detox as intervention. Digital detox can significantly improve mental health of students in educational settings.